The Application of Scramble Learning Model to Communicative Character and Learning Interests of Elementary School Students - Nanda Febbia Kavarela; Arief Cahyo Utomo (Jurnal Elementaria Edukasia, 2024)
Education plays an important role in everyone's life. Interest in learning is a factor that encourages students to be active in the teaching and learning process so that the learning process can achieve the expected goals. The research was motivated by the low interest in leraning PKn student of class II. The purpose of this study was to analyze the effect of the application of the scramble learning model on the communicative character and learning interest of students. Teachers need to be more focused in their learning activities, have a better understanding of learning challenges, and be able to use appropriate learning models in addition to paying attention to student learning interests. The learning model is very beneficial for both educators and learners. Learning models can serve as roadmaps and points of reference for educators as they apply learning methodically. Scramble cooperative learning is another approach to solving this problem. In this study, descriptive qualitative methods were used with qualitative research. Based on the results of the study, it was found that there was an increase in the results of students' learning interest and communication skills. Students are encouraged to talk, exchange ideas, and support each other in understanding and solving problems. Keywords: Communication Skills; Scramble Learning Model; PKn (Civic Education) Learning